2017
DOI: 10.1159/000458703
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Cytokines Produced by Stimulated CD3+ Cells from Chronic Myeloid Leukemia Patients

Abstract: Our work examined the production of intracellular interferon (INF)-γ, tumor necrosis factor (TNF)-α, interleukin (IL)-2, and IL-4 by in vitro stimulated CD3+ cells from 38 chronic myeloid leukemia (CML) patients. At the time of diagnosis the percentages of cells producing INF-γ, TNF-α, and IL-2 were strongly suppressed compared to those in healthy control subjects. Hematological remission achieved through treatment with tyrosine-kinase inhibitors was associated with a highly significant increase in the ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…1A). Our findings are in agreement with a previous report that demonstrated a strongly suppression of CD3+ cells producing TNF-α and INF-γ in whole blood samples of newly diagnosed CML patients [15]. Also, several studies have shown that NK-cell proportions among lymphocytes were decreased [11], and that T cells were functionally impaired displaying a decreased TCRζ-chain expression, a limited cytotoxic activity and a diminished production of Th1-cytokines (i.e.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…1A). Our findings are in agreement with a previous report that demonstrated a strongly suppression of CD3+ cells producing TNF-α and INF-γ in whole blood samples of newly diagnosed CML patients [15]. Also, several studies have shown that NK-cell proportions among lymphocytes were decreased [11], and that T cells were functionally impaired displaying a decreased TCRζ-chain expression, a limited cytotoxic activity and a diminished production of Th1-cytokines (i.e.…”
Section: Resultssupporting
confidence: 94%
“…Hematological remission was associated with a highly significant increase of CD3+ cells producing pro-inflammatory Th1 cytokines (i.e. INF-γ and TNF-α) [15] and this T cell response is sustained over time while in remission [12]. Also, patients with a complete cytogenetic response tend to a greater NK-cell reactivity [17].…”
Section: Resultsmentioning
confidence: 99%
“…However, data regarding the immune response of autologous T-cell from CML patients were contradicting. Some of the published data reported: 1) decreased in percentage Th1 and tumor necrosis factor (TNF)-α but increase in percentage of Th2 cytokine producing T cells [6][7][8]; 2) decreased in percentage of Th1 and TNF-α but comparable Th2 percentage of cytokine producing T cells [9]; or 3) decrease in percentage of both Th1 And Th2 of cytokine producing T cells from patients with untreated chronic phase CML [10,11]. Although Kiani et al [12] reported normal intrinsic Th1/Th2 balance secreted from purified CD4 T cells from patients with CP CML, they ruled out the presence of intrinsic T-cell defects.…”
Section: Introductionmentioning
confidence: 99%